(untitled) - Smart, Ninian (Cambridge,New York, 1998)
This book is a revised and updated edition of a popular work, which looks at the world's religions in terms of world history, and as constantly developing systems of belief. Part I traces the development of religions, as they evolved from the traditions of the ancient world. Part II examines the changes to faiths and cultures following the Renaissance and the voyages of conquest and discovery, and asks how, why, and with what effect religions have been refashioned over the ages up to today. In this richly illustrated new edition, religions are described through their symbols, rituals, followers, architecture and art. References, statistics, maps and pictures have been updated and added, illuminating the true nature of each religion. The text has been thoroughly revised to highlight recent developments, such as the spread of Islam, African-American and Hispanic-American religious experience, and women priests.
Keywords: Religions,Tôn giáo